Pengaruh Penyuluhan Senam Lansia Terhadap Minat Mengikuti Senam Lansia Tentang Masa Menopause Pada Usia 45-59 Tahun di Desa Bandar Setia Kabupaten Deli Serdang Tahun 2023. - Sinaga, Lia Rosa Veronika; Nadilla Pratiwi; Seri Asnawati Munthe; Jasmen Manurung (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
One way to improve functional abilities in the elderly is with elderly exercise, because the benefits of elderly exercise for health are as a promotive, preventive, curative and rehabilitative effort. These benefits can be seen physically, psychologically and socially. The physical benefits of exercise for the elderly can stabilize blood pressure, increase body endurance and maintain ideal body weight, strengthen bones and muscles, increase body flexibility and improve fitness. This research aims to find out whether there is an influence of elderly exercise education on interest in participating in elderly exercise regarding the menopause period at the age of 45-59 years in Bandar Setia Village, Deli Serdang Regency in 2023. In this research the author uses quantitative research in the form of pre-experimental design. This research is a one-group pretest-posttest design. The number of samples in this research was 37 respondents using the Slovin formula and the research instrument used a questionnaire. The results of this research were obtained before the elderly exercise education was carried out, the majority of respondents had a low interest of 27 people (73%), and a moderate interest of 10 people (27%). After counseling on exercise for the elderly, the majority of respondents had moderate interest, 21 people (56.8%), and 16 people (43.2%) had high interest. The results of statistical tests using the Wilcoxon test obtained a P value of 0.000. Where the value of α = 0.05 from these results when compared to the value of P < α then Ha is accepted, namely that there is an influence of elderly exercise counseling on interest in participating in elderly exercise regarding the menopause period at the age of 45-59 years in Bandar Setia village, Deli Serdang district in 2023.